NINE MOST COMMON MISCONCONCEPTIONS IN THE DIAGNOSIS AND TREATMENT OF GLAUCOMA - Bozic, Marija (Medical Research, 2025)
Diagnosis and treatment of glaucoma have advanced significantly in the last 20 years, but there are still some misconceptions about this group of diseases in everyday ophthalmological practice. The goal of this review is to point out the most common misconceptions in the diagnosis and treatment of glaucoma, which should improve the quality of treatment for our patients.A review of research articles with key words glaucoma, misconception, intraocular pressure measurement, published in PubMed database until June 30th, 2025 was done.Some of the most common misconceptions in the diagnosis and treatment of glaucoma are related to the method of measuring intraocular pressure, the time when the measurement is performed, subtracting/adding values according to the nomogram for pachymetry, banning caffeine intake for glaucoma patients and recommendations for physical activity in all forms of glaucoma.While significant advancements have been made in the diagnosis and treatment of glaucoma, persistent misconceptions among ophthalmologists must be addressed to improve patient outcomes and quality of life.
Keywords: glaucoma, diagnosis, treatment, error